Ion-conducting battery including solid electrolyte material

By using solid electrolyte materials with porous and high-density areas in lithium-ion batteries, the safety risks and insufficient energy density of existing lithium-ion batteries are solved, and battery performance with high safety and high energy density is achieved.

JP2025060603AInactive Publication Date: 2025-04-10UNIV OF MARYLAND
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024207408
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2013-03-21
Filing Date
2024-11-28
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium-ion batteries and other ionic conductive batteries have safety risks, such as combustible organic electrolytes, safety problems caused by battery interface reactions, and instability of organic electrolytes, which affect the output efficiency and life of the battery.

Method used

The solid-state ion conductive battery is used to use solid-state electrolyte materials with porous and high-density areas to ensure the safety and stability of the battery, and to improve the energy density and power density of the battery by introducing high-density and porous areas into the battery structure.

Benefits of technology

The battery is achieved with high safety and high energy density, reducing the risk of battery interface reaction and electrolyte decomposition, extending the battery's service life, and improving the battery's charging and discharging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060603000001_ABST
    Figure 2025060603000001_ABST
Patent Text Reader

Abstract

To provide a solid-state, ionically conductive battery with reduced electrode resistance.SOLUTION: A solid-state, ionically conductive battery includes an ionically conductive solid electrolyte, and the solid electrolyte has at least one porous region and a dense region. The battery is, for example, a lithium-ion, sodium-ion, or magnesium-ion conductive solid-state battery. The ionically conductive solid electrolyte is, for example, a lithium-garnet material. The solid-state, ionically conductive battery includes a cathode and an anode, at least one of which is disposed in a portion of the porous region.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is a joint venture of U.S. Provisional Application No. 61 / 803,981, filed March 21, 2013. No. 6,313,635, the disclosure of which is incorporated herein by reference. [Technical field]

[0002] The present disclosure relates generally to ion-conducting batteries containing solid electrolytes. [Background technology]

[0003] Lithium-ion batteries (LiB) are: It has the highest volumetric and gravimetric energy density, which makes LiBs the most versatile battery from portable electronic devices. The current LiB is mainly made up of Li Cathode of CoO2 or LiFePO4 type, Li + Conductive organic electrolytes (e.g., ethylene carbonate) LiPF6) dissolved in carbonyl-diethyl carbonate, and Li metal or Unfortunately, the current state-of-the-art LiBs have several limitations: There are technical problems: safety due to flammable organic components; anode and cathode Reactions occurring in electrolytes and interfaces (solid electrolyte interphase - SEI) decomposition due to the formation of compounds; and power / energy loss due to poor electrochemical stability of organic electrolytes. Energy density limit. Based on sodium, magnesium, and other ion-conducting electrolytes Other batteries that use 100% ethanol have similar problems. Summary of the Invention [Means for solving the problem]

[0004] A solid-state ionically conductive battery comprising: (a) a cathode or anode material; ) A solid-state electrolyte (SSE) material that includes a porous region having a plurality of pores and a dense (dense) region. wherein the cathode material or the anode material is present in at least a portion of the porous region. (c) the high density region is free of the cathode material and the anode material; a current collector disposed in contact with the cathode material or at least a portion of the anode material. battery.

[0005] In one embodiment, the SSE material comprises two porous regions and the battery comprises The cathode material and the anode material, the cathode material forming a cathode-side porous region. The anode material is disposed on at least a portion of one of the porous regions forming the anode side. The cathode side region is disposed in at least a part of the other porous region that forms the porous region. The anode side region and the anode side region are disposed on opposite sides of the high density region, and further The electrode-side current collector and the anode-side current collector are included.

[0006] In one embodiment, the cathode material is a lithium-containing material, a sodium-containing cathode material. or a magnesium-containing cathodic material. In one embodiment, the cathodic material is The cathode material may optionally further comprise an organic or gel-based conductive carbon material. In one embodiment, the lithium-containing electrode material is LiCoO 2. Lithium-containing ion-conducting material selected from LiFePO4 and Li2MMn3O8 The cathode material is selected from Fe, Co, and combinations thereof. In an embodiment, the sodium-containing cathodic material is Na2V2O5, P2-Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2, Na3V2(PO4)3, NaMn 1 / 3 Co 1 / 3 Ni 1 / 3PO4, and Na 2 / 3 Fe 1 / 2 Mn 1 / 2 From O2 and graphene composite In one embodiment, the sodium-containing ion-conducting cathode material is selected. The magnesium-containing cathode material is a magnesium-containing ion-conducting cathode material. , doped manganese oxide.

[0007] In one embodiment, the anode material is a lithium-containing anode material, a sodium-containing anode material, or In one embodiment, the lithium-containing anode material is a magnesium-containing anode material. In one embodiment, the sodium-containing anode material is lithium metal. The doped material is sodium metal, or Na2C8H4O4 and Na 0.66 Li 0.2 2Ti 0.78 O2. In one embodiment, the magnesium-containing anodic material is magnesium metal.

[0008] In one embodiment, the SSE material is a lithium-containing SSE material, a sodium-containing SSE material, In one embodiment, the lithium-containing SSE material is a magnesium-containing SSE material. The SE material is a Li-garnet SSE material. The SSE material is cation-doped Li5La3M 1 2O 12 (M 1 are Nb, Zr, Ta, or a combination thereof), cation-doped Li6La2BaTa2O 12 , Cacio Doped Li7La3Zr2O 12 , and cation-doped Li6BaY2M 1 2O 12 where the cation dopant is barium, yttrium, zinc, or In one embodiment, the Li-garnet SSE material is a combination of Li5L a3Nb2O 12 , Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6La 2SrNbO 12 , Li6La2BaNb2O 12 , Li6La2SrTa2O 12 , Li6La2BaTa2O 12 , Li7Y3Zr2O 12 , Li 6.4 Y3Zr 1.4 T a 0.6 O 12 , Li 6.5 La 2.5 Ba 0.5 TaZrO 12 , Li6BaY2M 1 2O 12 , Li7Y3Zr2O 12 , Li 6.75 BaLa2Nb 1.75 Zinc 0.25 O 12 , or Li 6.75 BaLa2Ta 1.75 Zinc 0.25 O 12 It is.

[0009] In one embodiment, the current collector is a conductive metal or metal alloy.

[0010] In one embodiment, the dense regions of the SSE material have dimensions between 1 μm and 100 μm; and / or the porous region of the SSE material in which the cathode material is disposed is less than 20 μm. and / or the SS on which the anode material is disposed. The porous regions of the E material have dimensions between 20 μm and 200 μm.

[0011] In one embodiment, the ion-conducting cathode material, the ion-conducting anode material, The SSE material and the current collector form a cell, and the solid ionically conductive battery Lee has a plurality of such cells, and each adjacent pair of the cells is a bipolar plate. are separated by

[0012] A solid electrolyte (S) comprises a porous region of electrolyte material disposed on a dense region of electrolyte material. In a solid-state ionically conductive battery having a SSE material, the SSE material is an ion diffuses into the porous region of the SSE material during charging and / or discharging of the battery. In one embodiment, the SSE material is configured to diffuse from the The SSE material has two porous regions disposed on either side (opposite sides) of a dense region. [Brief description of the drawings]

[0013] The following drawings are provided for illustrative purposes only and are therefore not intended to limit the scope of the present disclosure. Not intended.

[0014] [Figure 1]Figure 1 shows the ionic conductivity vs. diffusion coefficient for garnet-type compounds: (1) Li5La3Ta2O12, (2) Li5La3Sb2O12, (3) Li5La3Nb2O12, (4) Li5.5BaLa2Ta2O11.75, (5) Li6La2BaTaO12, (6) Li6.5BaLa2Ta2O12.25, (7) Li7La3Zr2O12, (8) Li6.5La2.5Ba0.5TaZrO12 (sintered at 900°C), and (9) Li6.5La2.5Ba0.5TaZrO12 (sintered at 1100°C).

[0015] [Diagram 2] Examples of optimization of Li-ion conduction in garnet-type solid electrolytes (SSEs): (a) and (b) Li+ conduction pathways; (c) influence of Li+ site occupancy on conductivity.

[0016] [Diagram 3] FIG. 3 is a schematic diagram of one embodiment of a solid-state lithium battery (SSLiB) showing a thin (~10 μm) garnet SSE layer spread as a tailored nano / microstructured scaffold within the anode (Li metal loaded) and cathode (Li2MMn3O8 [M=Fe, Co] mixed with graphene) to provide structural support for the solid electrolyte (SSE) layer, and high surface area and continuous ion transport pathways to reduce polarization. A general-purpose ~40 μm Al current collector (with ~200 Å Cu on the anode side) provides strength and thermal and electrical conduction. ~170 μm repeat units are stacked in series to provide the desired battery pack voltage and strength (a 300 V pack can be less than 1 cm thick). The highly porous SSE scaffold creates a large interfacial area that significantly reduces cell impedance.

[0017] [Figure 4] (a) Ionic conductivity of an example of Li-garnet. (b) PXRD of an example of Li6.75La2BaTa1.75Zn0.25O12.

[0018] [Diagram 5] 5 is an electrochemical impedance spectroscopy (ESI) of an example SSE battery with a LiFePO4 cathode (20% carbon black), dense SSE, Li-infiltrated SSE framework, and Al current collector. The absence of an additional low frequency intercept indicates that the electrolyte interface is reversible to Li ions.

[0019] [Figure 6] FIG. 6 shows the PXRD, SEM images and conductivity showing the formation of garnet-type Li6.75La2BaTa1.75Zn0.25O12 as a function of temperature, indicating that the sintering temperature can control the density, grain size and conductivity.

[0020] [Figure 7] FIG. 7 shows examples of multilayer ceramic processing: (a) tape cast support; (b) thin electrolyte on layered porous anode support with a bimodally integrated anode functional layer (BI-AFL); (c) close-up of the BI-AFL demonstrating the ability to integrate nanoscale features to reduce interfacial impedance using conventional ceramic processing.

[0021] [Figure 8] (a) Cross-section and (b) plan view of an example of an SSE with a porous scaffold (filled with anode and cathode materials). (c) Cross-section of the SSE scaffold after Li metal infiltration. (d) Cross-section of the Li metal-dense SSE interface. The images demonstrate that Li wetting of the SSE was excellent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present disclosure provides an ion-conducting battery having a solid electrolyte. Terry has developed a lithium-ion solid electrolyte battery and a sodium-ion solid electrolyte battery. Terry, magnesium ion-solid electrolyte battery. Lithium ion (Li+ )- Batteries are used, for example, in portable electronic devices and electric vehicles, and contain sodium Ion (Na + )-batteries are powered by intermittent renewable energy sources, such as solar and wind. - Used for electrical grid storage to enable deployment, magnesium ions (Mg 2+ ) -The battery is Mg 2+ Since each ion is twice as charged, Li + and Na + It is predicted to have better performance.

[0023] Solid-state batteries have advantages over conventional batteries. For example, solid electrolytes: Non-flammable and highly safe, enabling high voltage electrodes for greater energy density The battery design (Figure 3) uses a thin electrolyte layer and a larger Both of these allow for lower resistance and therefore a larger electrolyte / electrode interfacial area. Further, the structure provides the additional advantage of providing high power and energy density. The structure is resistant to mechanical stress from ion intercalation during charge and discharge cycles, and reducing the formation of the interphase solid electrolyte (SEI) layer, thus extending the lifespan of current battery technology. Eliminate life-limiting capacity-depletion mechanisms.

[0024] The solid-state battery comprises a cathode material, an anode material, and an ion-conducting solid electrolyte. The solid electrolyte material includes a dense region (e.g., a layer) and one or more The porous region (or regions) is / are located on one side of the dense region. The high density region and the high density region may be disposed on opposite sides (both sides). The porous region or regions are made from the same solid electrolyte material. For example, lithium ions, sodium ions, or magnesium ions can be transferred. Lead.

[0025] The cathode is in electrical communication with a porous region of the ionically conductive solid electrolyte material. For example, the cathodic material may be a material that is capable of reacting with the electrolyte by a mechanism such as intercalation. ions that store ions by the mechanism or react with ions to form secondary phases. The cathode material is an ion-conducting material (e.g., air or sulfide electrodes). Examples of suitable cathode materials are: It is known in the art.

[0026] The cathode material, if present, is a porous region of the ionically conductive solid electrolyte material. The cathode is disposed on at least a portion of the surface of the cathode (for example, on a surface of one of the pores). The material, if present, is a porous region of the ionically conductive solid electrolyte material or At least partially filling one or more pores (e.g., a majority of the pores) of one of the plurality of porous regions. In one embodiment, the cathode material is a porous layer of the ionically conductive solid electrolyte material. Infiltrating into at least a portion of the plurality of pores of the region.

[0027] In one embodiment, the cathode material comprises a porous region of an ion-conducting SSE material. a porous region of the ion-conducting SSE material disposed on at least a portion of the pore surface on the side of the ion-conducting SSE material; The cathode side of the SSE is a porous region of ion-conducting SSE material in which the anode material is disposed. It faces the anode side.

[0028] In one embodiment, the cathode material is a lithium ion conducting material. Lithium ion conductive cathode materials are LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 Lithium nickel manganese oxide etc. Lithium oxide (NMC, LiNi x Mn y Co z O2, x+y+z=1), LiMn2O4 etc. Lithium manganese oxide (LMO), LiNi 0.5 Mn 1.5 O4, LiFePO4, etc. Lithium iron phosphate (LFP), LiMnPO4, and LiCoPO4, and Li2MM n3O8, where M is selected from Fe, Co, and combinations thereof. In one embodiment, the ion-conducting cathode material is a high energy ion-conducting material such as Li2MMn3O8. a conductive cathode material, where M is selected from Fe, Co, and combinations thereof; will be done.

[0029] In one embodiment, the cathode material is a sodium ion conducting material. The sodium ion conducting cathode material is Na2V2O5, P2-Na 2 / 3 Fe 1 / 2Mn 1 / 2 O2, Na3V2(PO4)3, NaMn 1 / 3 Co 1 / 3 Ni 1 / 3 PO4 and Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2-graphene-composite, etc. and composite materials (e.g., composites with carbon black).

[0030] In one embodiment, the cathode material is a magnesium ion conducting material. For example, The magnesium ion conducting cathode material is doped manganese oxide (e.g., Mg x Mn O2· y H2O).

[0031] In one embodiment, the cathode material is an organic sulfide or polysulfide. Examples of organic sulfides include carbyne polysulfides and copolymerized sulfur.

[0032] In one embodiment, the cathode material is a cathode. Examples of materials suitable for the cathode include metal oxides, High surface area carbon nanotubes bound to a polymer binder (e.g., PVDF binder) Carbon particles (e.g., Super P, a conductive carbon black) and catalyst particles (e.g., α-M nO2 nanorods) are used in solid-state lithium-ion batteries with air cathodes. This includes those that can be used.

[0033] It is desirable to use an electrically conductive material as part of the ionically conductive cathode material. In embodiments, the ion-conducting cathode material is a conductive carbon material (e.g., graphene or The ion-conducting cathode material may also include an organic Alternatively, the conductive material may include a gel ion-conducting electrolyte. For example, a conductive material (e.g., graphene) may be separate from the ion implantation material. At least a portion of the surface (e.g., pore surface) of the porous region of the silicon-sulfide electrolyte material is disposed on the surface of the porous region. The ionically conductive cathode material is preferably at least one of the electrically conductive material (e.g., graphene). At least a part of it is in contact with the

[0034] The anode is an anode in electrical contact with the porous region of the ion-conducting SSE material. For example, the anode material may be an indium ion implantable in the form of a metal that is conductive to the solid electrolyte. on (e.g., metallic lithium for lithium-ion batteries) or Compounds that intercalate ions (e.g., lithium carbide for lithium-ion batteries) Examples of suitable anode materials are known in the art.

[0035] The anode material, if present, is a surface of the porous region of the ion-conducting SSE material. The anode material is disposed on at least a portion of the surface (for example, on a surface of one of the pores). If present, the ion-conducting SSE electrolyte material is ionically conductive and is formed in one or more pores (e.g., In one embodiment, the anodic material at least partially fills the pores (e.g., the majority of the pores). infiltrating into at least a portion of the plurality of pores of the porous region of the ionically conductive solid electrolyte material; There are.

[0036] In one embodiment, the anode material comprises an ionically conductive SSE electrolyte material on the anode side. and an ion-conducting solid electrolyte material disposed on at least a portion of the pore surfaces of the porous region. The anode side of the porous ion-conducting SSE is connected to the cathode side of the porous ion-conducting SSE (wherein the cathode material It faces the 100mm F2.0 in which the 100mm F2.0 is located.

[0037] In one embodiment, the anode material is a lithium-containing material. The material is lithium metal, or Li4Ti5O 12 Lithium titanate (LTO) and other ion The anode material is a conductive lithium-containing anode material.

[0038] In one embodiment, the anode material is a sodium-containing material. The base material is sodium metal, or Na2C8H4O4 and Na 0.66 Li 0.22 Ti 0.78 Ionically conductive, such as O2-containing anode materials.

[0039] In one embodiment, the anode material is a magnesium-containing material. The node material is magnesium metal.

[0040] In one embodiment, the anode material is selected from the group consisting of graphite, hard carbon, porous hollow carbon spheres, and and tubes, and tin and its alloys, tin / carbon, tin / cobalt alloys, or a conductive material such as silicon / carbon.

[0041] The ionically conductive solid electrolyte material comprises a dense region (e.g., a dense layer) and a or two porous regions (e.g., porous layers). The porosity of the dense region is In one embodiment, the dense region is less than the porosity of the porous region(s). The cathode material and / or the anode material are not porous. Separate (separate) cathode material-containing regions and / or separate anode material-containing regions of material The ion-conducting solid electrolyte is disposed in the porous region of the forming SSE material. Each of these regions of material may be independently between 20 μm and 200 μm (and all integers therebetween). having a dimension (e.g., thickness perpendicular to the longest dimension of the material) of 1000 microns or less (including values ​​and ranges of 1000 microns or less) .

[0042] The dense and porous regions described herein are separate (discrete) dense and porous layers. In one embodiment, the ion-conducting solid The electrolyte material has one dense layer and one or two porous layers.

[0043] The ionically conductive solid electrolyte material transports ions (e.g., lithium) between the anode and the cathode. The ions that conduct electricity are lithium ions, sodium ions, or magnesium ions. The conductive solid electrolyte material does not have pinhole defects. The ionically conductive solid electrolyte material for the cell is selected from the same ionically conductive solid electrolyte material. One or more porous regions (e.g., porous layers) (said porous regions / layers are referred to herein as A dense region (e.g., a single region) supported by a single vertex (also called a scaffold) It has a high density layer.

[0044] In one embodiment, the ionically conductive solid electrolyte comprises a single dense region (e.g., a dense The porous region has a high density layer and two porous regions (e.g., a porous layer), the porous region being adjacent to the high density region. a cathode material is disposed on one side of said porous region and an anode material is disposed on the other side of said porous region. is disposed in the other porous region.

[0045] In one embodiment, the ionically conductive solid electrolyte comprises a single dense region (e.g., a dense a porous region (e.g., a porous layer) and a high density region (e.g., a high porosity region), a cathode material or an anode material is disposed on one side of the porous region; If the cathode material is placed in the porous region, the conventional battery - anode (e.g., a conventional solid-state battery anode) is formed in said high density region by known methods When the anode material is placed in the porous region, the conventional barrier A battery cathode (e.g., a conventional solid-state battery cathode) is disposed opposite the high density region. is formed.

[0046] The porous region (e.g., porous layer) of the ionically conductive solid electrolyte material may be a porous structure. The porous structure has microstructural features (e.g., microporosity) and / or nanostructures. For example, each porous region may independently have a pore size of 10 In another example, the porosity is from about 100% to about 90% (including all integer % values ​​and ranges therebetween). Each porous region may be independently porosity between 30% and 70% (and all integer percentages and ranges therebetween). When two porous regions are present, the porosity of the two layers is the same. The porosity of the individual regions may be different, for example, depending on subsequent screen printing or To accommodate the processing step in the wetting step (e.g., higher porosity, The electrode material (e.g., charge storage material (e.g., cathode)) is easier to fill, and the desired Electrode material capacity (i.e., how much conductive material (e.g., Li, Na, Mg) is in the electrode material) The porous region (e.g., , layer) to reduce the thickness of the dense layer and thereby reduce its resistance, The porous layer also provides structural support to the dense phase (solid The ionic conduction of the electrolyte is extended into the electrode layer, and the ionic conduction through the electrode and the electrode / electrode The electrode resistance is reduced from the viewpoints of both the charge transfer reaction at the electrolyte interface and the interface resistance. The effect is improved by having a larger electrode / electrolyte interfacial area.

[0047] In one embodiment, the solid-state, ionically conductive electrolyte material is a solid-state electrolyte lithium-containing material. For example, the solid electrolyte lithium-containing material is a lithium-garnet SSE material. be.

[0048] In one embodiment, the solid-state, ionically conductive electrolyte material is a cation-doped Li5La3M '2O 12 , cation-doped Li6La2BaTa2O 12 , cation-doped Li7La 3ZrO 12 , and cation-doped Li6BaY2M'2O 12 Li-Ga2O3 The cation dopants are barium, yttrium, zinc, or a combination thereof, and M' is Nb, Zr, Ta, or a combination thereof. It is a combination.

[0049] In one embodiment, the Li-garnet SSE material is Li5La3Nb2O 12、 L i5La3Ta2O 12 , Li7La3Zr2O 12 , Li6La2SrNb2O 12 , Li6La2BaNb2O 12 , Li6La2SrTa2O 12 , Li6La2BaTa 2O 12 , Li7Y3Zr2O 12 , Li 6.4 Y3Zr 1.4 Ta 0.6 O 12 , Li 6.5 La 2.5 Ba 0.5 TaZrO 12 , Li6BaY2M 1 2O 12 , Li7Y3 ZrO 12、Li 6.75 BaLa2Nb 1.75 Zinc 0.25 O 12 , or Li6 .75 BaLa2Ta 1.75 Zinc 0.25 O 12 Includes.

[0050] In one embodiment, the solid, ionically conductive electrolyte material is a sodium-containing solid electrolyte material. For example, a sodium-containing solid electrolyte is Na3Zr2Si2PO 12 (NASI CON) or β-alumina.

[0051] In one embodiment, the solid, ionically conductive electrolyte material is a solid electrolyte magnesium-containing material. For example, the magnesium ion conductive electrolyte material is MgZr4P6O 24 in be.

[0052] The ion-conducting solid electrolyte material is a dense region that does not include the cathode material and the anode material. For example, this range can be from 1 μm to 100 μm (and all integer microns in between). In another example, the material has a dimension (e.g., a thickness perpendicular to the longest dimension of the material) including values ​​and ranges. , this region has dimensions between 5 μm and 40 μm.

[0053] In one embodiment, the solid state battery comprises a lithium-containing cathode material and / or a lithium The battery includes a lithium-containing anode material, and a lithium-containing, ion-conducting, solid electrolyte material. In one embodiment, the solid-state battery comprises a sodium-containing cathode material and / or a sodium-containing In one embodiment, the anode material comprises a sodium-containing, ionically conductive, solid electrolyte material. The solid-state battery comprises a magnesium-containing cathode material and / or a magnesium-containing an anode material, and a magnesium-containing, ion-conducting solid electrolyte material.

[0054] The solid ionically conductive electrolyte material is a material that contains ions (e.g., lithium ions, sodium ions, etc.). ions, or magnesium ions) are added to the solid ion during charging and / or discharging of the battery. Diffusion into and out of porous regions (e.g., porous layers) of the ionic conductive electrolyte material. In one embodiment, the solid-state ionically conductive battery is configured to (e.g. lithium ion, sodium ion, or magnesium ion) in the battery The porous region(s) of the solid ionically conductive electrolyte material during charging and / or discharging of the One or two porous regions (e.g., The solid ionically conductive electrolyte material includes a porous layer.

[0055] Those skilled in the art will appreciate that numerous techniques are available for processing / forming the porous, solid, ionically conductive electrolyte material. Treatment methods (high-temperature solid reaction process, co-precipitation process, hydrothermal process, sol-gel process, etc.) will understand that it is known.

[0056] The materials can be systematically synthesized by solid state mixing techniques. For example, starting materials The mixture of substances may be mixed in an organic solvent (e.g., ethanol or methanol); The mixture of starting materials is dried to drive off the organic solvent. The mixture after ball milling may be calcined. The mixture after ball milling was heated to a temperature between 500°C and 2000°C (and all integer values ​​in between). and ranges inclusive) for at least 30 minutes to at least 50 hours. The mixture is then mixed with stabilized zirconia or alumina to achieve the required particle size distribution. The calcined mixture may be milled using a medium such as pulverized water or other medium known to those skilled in the art. For example, the calcined mixture may be sintered at a temperature between 500°C and 2000°C (or (including all integer values ​​and ranges between 0 and 100°C) for at least 30 minutes to at least 50 hours. To achieve the required particle size distribution, the calcined mixture is subjected to vibratory milling, Such as friction milling, jet milling, ball milling, or another technique known to those skilled in the art. using techniques such as stabilized zirconia, alumina, or other media known to those skilled in the art. The body may be used to crush.

[0057] Those skilled in the art will recognize that a number of conventional fabrication and processing methods are available for the above-mentioned processes for the green form (unsintered state). It will be appreciated that it is known to fabricate ionically conductive SSE materials such as Such methods include tape casting, calendaring, embossing, punching, etc. Laser cutting, solvent bonding, lamination, heat lamination, extrusion, co- Extrusion, Centrifugal Casting, Slip Casting, Gel Casting, Die Casting, pressing, isostatic pressing, hot isostatic pressing, uniaxial pressing, and The resulting green foam includes, but is not limited to, sol-gel and sol-gel processes. The material is then cooled to room temperature in order to minimize the loss of the individual components of the ionically conductive SSE material. or techniques known to those skilled in the art, such as conventional heat treatment in a controlled atmosphere. The ion-conducting SSE material may be sintered using the same method as in the embodiment of the present invention. In some embodiments, the green is molded by die pressing, optionally followed by isostatic pressing. It is advantageous to fabricate the ionically conductive SSE material in a tungsten-based form. Casting, punching, laser cutting, solvent bonding, heat lamination, or other techniques known to those skilled in the art, to produce green foam multilayers. It would be advantageous to fabricate ion-conducting SSE materials as channel devices.

[0058] Standard X-ray diffraction analysis techniques have revealed the crystal structure and structure of the solid sodium electrolyte in the fired ceramic membrane. This may be performed to identify the purity and phase of the sample.

[0059] The solid-state battery (e.g., lithium ion solid electrolyte battery, sodium ion A lithium-ion solid electrolyte battery, or magnesium-ion solid electrolyte battery, is a battery that uses a current collector ( The battery includes a porous solid electrolyte material disposed on the cathode side. A cathode (first) current collector is placed on the anode side of the porous solid electrolyte material. The anode side (second) current collector is made of a metal (e.g., aluminum, copper, or or titanium) or metal alloys (aluminum alloys, copper alloys, or titanium alloys), respectively. are made independently.

[0060] The solid-state battery (e.g., lithium ion solid electrolyte battery, sodium ion The magnesium-ion solid electrolyte battery (MEA), also known as the magnesium-ion solid electrolyte battery, is a Further components (bipolar plates, sheath, electrical contacts / leads for connecting wires, etc.) In one embodiment, the battery further comprises a bipolar plate. In one embodiment, the battery further comprises a bipolar plate and a sheath, and a wire for connecting the bipolar plate and the sheath. In one embodiment, the repeating unit of the battery cell includes a bipolar It is separated by a plate.

[0061] the cathode material (if present), the anode material (if present), the SSE material the cathode side (first) current collector (if present), and the anode side (second) current collector (if present). In this case, the solid ion conductive battery may form one cell. The battery has a number of cells separated by one or more bipolar plates. The number of cells in a battery is determined by the performance requirements (e.g., voltage output) of the battery. For example, the solid-state ion conductive battery is limited only by the above constraints. Includes 00 cells (including all integer valued cells and ranges in between).

[0062] In one embodiment, the ionically conductive solid-state battery or battery cell comprises one planar With a planar cathode and / or anode-electrolyte interface or with a planar cathode and / or In one embodiment, the battery or battery The cell does not exhibit an interphase solid electrolyte (SEI).

[0063] The following examples are presented to illustrate the present disclosure. They are not intended to be limiting in any way. Nor is this intended. EXAMPLES

[0064] The following are examples illustrating the solid-state lithium-ion batteries of the present disclosure and their manufacture. do.

[0065] The flammable organic electrolytes in conventional batteries, for example, -3 Scm -1Above room temperature A non-flammable ceramic system exhibiting high ionic conductivity at low temperatures and electrochemical stability up to 6V They can be replaced with solid-state electrolytes (SSEs), which further increase the power / energy density. To increase the charge transport, a typical LiCoO2 cathode was replaced with a higher voltage cathode material. Furthermore, this in a planar stack structure with a metal current collector is possible. The integration of these ceramic electrolytes would provide battery strength.

[0066] Inherently safe, robust, low-cost, high-energy-density all-solid-state Li-ion batteries Terry (SSLiB) - Highly conductive garnet-type solids in tailored micro / nano structures By incorporating a Li-ion electrolyte and a high-voltage cathode, This battery is made using thin-film ceramic technology. Can be used.

[0067] For example, ~10 -3 Scm -1 Li- with room temperature (RT) conductivity of 0.01% (same as organic electrolytes) Garnet solid electrolytes (SSEs) can be used, which increase the disorder of the Li-sublattice. By doing this, ~10 -2 Scm -1 The high stability garnet The SSE is a Li2MMn3O8 (M=Fe, Co) high voltage (~6V) cathode and a Li metal anode. This allows the nodes to be used without concerns about stability or flammability.

[0068] Known fabrication techniques produce a resistance of only ~0.01 Ωcm -2 The area specific resistance (ASR) of It can be used to form highly supported thin film (~10μm) SSEs. Scalable The use of a simple multi-layer ceramic fabrication technique reduces manufacturing costs without the need for drying chambers or vacuum equipment. can be dramatically reduced.

[0069] In addition, tailored micro / nano-structured electrode supports (scaffolds) increase the interfacial area and Overcoming the high impedance inherent to planar solid-state lithium-ion batteries (SSLiB) This results in a C / 3 IR drop of only 5.02mV. The charging / discharging of the Li-anode and Li2MMn3O8 cathode frameworks by It provides high depth of discharge capability without the mechanical cycling fatigue seen in

[0070] At ~170μm / repetition unit, a 300V battery pack is just under 1cm thick. This form factor, with its high strength due to the aluminum bipolar plate, is suitable for frame and element construction. This allows for synergistic placement between components, reducing effective weight and volume. Based on the design, targeted SSE conductivity, high voltage cathode, and high capacity electrode, the expected effectiveness The specific energy is ~600Wh / kg at C / 3, including the structural bipolar plate. This is essentially external since the bipolar plates provide the strength and temperature control is not essential. This is a complete battery pack specification excluding the can. The corresponding effective energy density is 1810W h / L.

[0071] All manufacturing steps are carried out without the need for dry chambers, vacuum deposition, or glove boxes. It can be done in ambient air using conventional ceramic processing equipment, dramatically reducing production costs. to reduce it.

[0072] All solid-state batteries that do not contain SEI or current state-of-the-art Li batteries For other degradation mechanisms available, the calendar life of an instant battery is It is expected to last in excess of 10 years, with a cycle life expected to exceed 5000 cycles.

[0073] Solid Li-garnet electrolyte (SSE) is ~10 -3 Scm -1 Room temperature (RT) conductivity ( equivalent to the machine electrolyte) and high voltage (~6V) cathode and lithium metal anode (flammable suspension) It has unique properties that make it SSLiB unique, including stability against

[0074] The use of SSE oxide powders allows the electrode-supported thin films (~ Use of low-cost, scalable multilayer ceramic fabrication techniques to form (10 μm) SSEs Similarly, engineered micro / nano-structured electrode supports dramatically increase the interfacial area. The latter overcomes the high interface impedance inherent to the planar SSLiB structure and is Provides high depth of discharge capability without the mechanical cycling fatigue seen with electrodes and SEI layers Avoid formation.

[0075] The scaffold / electrolyte / scaffold structure of the SSE also provides mechanical strength, which is the strength between the planar cells. Allows the incorporation of structural metal interconnects (bipolar plates) for strength, weight, thermal uniformity, and The resulting strength and form factor improves the battery pack. provides the potential for load-bearing.

[0076] High Li + The garnet-type solid electrolyte with high conductivity and high voltage stability is Li5La3Ta2O 12 , Li6La2BaTa2O 12 and Li7La3Zr2O 12 Ta and Z in r can be doped with certain cations, increasing the RT conductivity to ~10 -3 From 10 -2 Scm -1 The desirable conductivity, ionic transport number, and elemental Li Compositions can be found that have electrochemical stability up to 6V.

[0077] Electrode-supported thin film SSE can be fabricated. Submicron SSE powder and its SSE ink / Paste formulations can be made by tape casting, colloidal deposition, and sintering. The conditions were set to form a dense thin film (~10 μm) garnet SSE on a porous scaffold. It can be developed into.

[0078] The cathode and anode can be integrated. Electrode-SSE interface structure and SSE The surface is optimized to minimize interfacial impedance for the targeted electrode composition. The high-voltage cathode ink is a high-voltage cathode incorporated in the SSE framework. It can be prepared to produce an SSLiB with a Li metal anode. Electrochemical performance of SLiBs including CV, energy / power density and cycling performance It can be determined by measurement.

[0079] It is possible to construct a stacked multi-cell SSLiB with Al / Cu bipolar plates. The energy / power density, size, and power density can be calculated as a function of the layer thickness and area of ​​the stacked multi-cell SSLiB. The life span and mechanical strength can be determined.

[0080] Li-filled garnet SSE The conductivity of the Li-garnet SSE depends on the Li content (stuffing) in the garnet structure. This can be improved by doping to increase the SSE. exhibit desirable physical and chemical properties, including: ·Cubic shaped Li7La3Zr2O 12 RT bulk conductivity (~10 -3 S / c m) High electrochemical stability for high voltage cathodes (up to 6V), approximately 2 times faster than current organic electrolytes High V, about 1V higher than the more common LiPON. Excellent chemical stability in contact with elemental and molten Li anodes (up to 400°C) Li + The transport number is close to a maximum value of 1.00, which is important for battery cycle efficiency. significant, whereas typical polymer electrolytes have a mere .about.0.35. Wide operating temperature capability, electrical conductivity increases with increasing temperature (0.1Scm at 300℃) -1 (The conductivity of polymer electrolytes is 0.25 to 1.5 kPa and remains appreciable below 0 °C.) In contrast, polymer electrolytes is flammable at high temperatures. - Synthesis can be performed by simply mixing oxide powders in air, thus scalable to bulk synthesis is easy.

[0081] Garnet SSE Li + The conductivity can be further increased. Ionic conductivity is determined by the Li + Figure 1 shows the correlation between the concentration of various Li -For filled garnets, Li + The relationship between conductivity and diffusion coefficient is shown. The conductivity is It increases with Li content, e.g., the cubic Li7-phase (Li7La3Zr2O 12)teeth , 5×10 -4 The RT conductivity in S / cm is shown. However, the conductivity includes the sintering temperature. The effect of composition and synthesis method is also dependent on the scaffold-supported SSE layer. And ~10 -3 The minimum RT conductivity of L S / cm can be determined. Through doping to increase the i-sublattice disorder, the RT conductivity can be increased to ~10 -2 S / cm. Ionic conduction in the garnet structure is expected to occur around the metal-oxygen octahedron. The site occupancy of Li ions at tetrahedral vs octahedral sites is related to the Li ion conduction The rate is directly controlled (Figure 2). For example, Li5La3Ta2O 12 So, about 80% Li ions occupy tetrahedral sites, and only 20% occupy octahedral sites. Octahedral sites Li + Increasing the concentration and decreasing the occupancy of the tetrahedral sides leads to an order of magnitude increase in ionic conductivity. It was shown that it is chemically stable in contact with elemental lithium and is equivalent to La (Fig. 2b). The smaller radius metal ion (e.g., Y 3+ ) increases the ionic conductivity To this end, a new series of garnets (Li6BaY2M2O 12 , Li 6.4 Y3Zr1 .6 Ta 0.6 O 12 , Li7Y3Zr2O 12 and its solid solutions) The enthalpy of formation of Y2O3 (-1932 kJ / mol) is This is lower than that of La2O3 (-1794 kJ / mol), and therefore the doping of Y into La The binding will increase the Y-O bond strength and weaken the Li-O bond. Due to the interaction energy between lithium and oxygen, Li + The mobility of Y increases. Due to its smaller ionic radius, ionic conduction around the metal oxygen octahedron is smoother. This is expected to provide a convenient pathway for

[0082] Another approach is Li6BaY2M2O 12 M 5+ M the site 2+ Cation ( For example, Zn 2+ , known to form distorted metal-oxygen octahedra, 3d o Kachi ZnO can be substituted with ZnO to further increase the concentration of mobile Li ions in the structure. It is believed that each M plays a role in both further increasing the sintering temperature and decreasing the final sintering temperature. 2 + is three Li for charge balance. + These ions are added to the vacancies in the garnet structure. Li + Thus, further Li + The increase in conductivity is due to the crystal structure, Li- To control site occupancy and minimize the activation energy of the conductive pathway, It can be obtained by modifying the garnet composition.

[0083] Due to the ceramic powder properties of Li-garnet, SSLiB uses conventional manufacturing techniques. This has significant advantages in terms of both cost and performance. All manufacturing steps are carried out in ambient air using conventional ceramic processing equipment in a dry chamber. It can be done without the need for vacuum deposition or a glove box, dramatically reducing manufacturing costs Reduce to.

[0084] The SSLiBs studied so far have been characterized by their low surface area, planar electrode / electrolyte interfaces ( For example, LiPON-based SSLiB suffers from high interface impedance. Low area specific resistance (ASR) cathodes and anodes increase the electrolyte / electrode interfacial area, To further extend the electrochemically active area from the electrolyte / electrode-planar interface, This can be achieved by incorporating nano / micro phases at the electrolyte / electrode interface. Modification of the structure (e.g., by colloidal deposition of powders or salt solution impregnation) improves the overall cell surface area. The overall specific resistance (ASR) can be reduced, resulting in a These same developments are likely to result in increased power density for the SSLiB interface. SSLiB can be applied to reduce impedance by known manufacturing techniques. Low-cost, high-speed, scalable multilayer ceramic processing allows for targeted nano-fabrication. Utilized to fabricate thin film (~10 μm) SSEs supported on nano / microstructured electrode scaffolds. SSEs with tailored porosity (nano / micro features) of ~50 and 70 μm are used. The garnet support layer (skeleton) is formed by tape casting followed by ~10μm of high density garnet. The resulting pinholes are obtained by colloidal deposition and sintering of the SSE layer. The SSE layer without any gap is mechanically robust due to the support layer and has low area specific resistance (ASR) (e.g. Only ~0.01Ωcm -2 Li2MMn3O8 is considered to have a porous structure. The first Li metal is screen printed into the porous cathode scaffold and the second Li metal is contained within the porous anode scaffold. For example, Li2(Co,Fe)Mn3O8 high voltage cathodes are produced by the wet chemical method. The nano-sized electrode powders are prepared in the form of nano-sized powders using a method similar to that of graphene. It is mixed with a conductive material such as carbon black and a polymer binder in NMP solvent. A typical mass ratio of the cathode, conductive additive or binder is 8:1 by weight. The viscosity of the slurry was optimized to fill the porous SSE scaffold. The Li nanoparticles can be immersed in a Li metal flashing solution, wetted in the solution, and dried. The Li may be infiltrated into the porous anode framework or the Li may be subjected to a dry room treatment. It may be provided sufficiently from the cathode composition so that this can be avoided.

[0085] Another major advantage of this structure is that the charge / discharge cycle is Rather than intercalating and expanding the fibers, the filling / voiding of the pores of the SSE scaffold is involved. As a result, the electrode dimensions during the charged and discharged states are likely to change. This would eliminate both cycle fatigue and depth of discharge limitations. The former allows for a longer cycle life, while the latter allows for a larger battery capacity. to.

[0086] Additionally, the overall cell size allows batteries to be stacked as structural units. There is no change in the current collector. The lightweight, ~40 micron thick Al plate serves only as a current collector. The ~20 nm Cu provides electrochemical compatibility with Li, The anode side may be electrodeposited. The bipolar current collector plate is then placed on the anode side until the slurry is completely dried. can be applied before the bipolar current collector is bonded to improve electrical contact between the bipolar current collector and the electrode material. It can be pressed for

[0087] SSLs with solid-state chemistry that is inherently safer compared to current LiBs with organic electrolytes iB not only increases non-energy density and reduces its cell-level cost, This is thought to avoid demanding package-level and system-level engineering requirements. High specific energy density at both cell and system level compared to state of the art can be achieved by: The stable electrochemical potential window of the garnet SSE allows for high cell voltages (~6V). This allows for pressure cathode. The porous SSE scaffold enables the use of Li-metal anodes with high specific capacity. The porous 3D networked SSE framework provides electrode materials with smaller charge transfer resistance. This allows for volumetric filling of 0.1% to 1.0% and increases the mass % of active electrode material. Bipolar plates are formed by electroplating ~200Å Cu on ~40μm Al plates. Considering that the density of Al is three times lower than that of Cu, the resulting plate is It weighs the same as the combined weight of ~10μm Al and Cu foils used in conventional batteries. However, it has 3 times the strength (the strength-to-weight ratio of Al is ~9 times higher than that of Cu). Because it is hot). · Repeating units (SSLiB / Bipolar plates) to obtain the desired battery pack voltage are then stacked in series (e.g. 50 for a 300V battery pack). (A 6V SSLiB would be less than 1cm thick.) Thermal and electrical control / management systems are not required as there is no concern about thermal runaway. The proposed intrinsically safe SSLiB also dramatically reduces the need for mechanical protection.

[0088] Energy density is 1cm2 Calculated from the thickness of the components of the device structure normalized to their area. The estimated SSE framework porosity is 70% for the cathode and 40% for the anodized one (Fig. 4) (see data in Table 1). The charge / capacity is balanced for the anode and cathode as follows: Keep:m Li ×C Li =m LMFO ×C LMFO (LFMO is Li2FeMn3O8 Therefore, the total mass (cathode-skeleton / SSE / skeleton and bipolar plate) is c m 2 This works out to 50.92 mg per area. To avoid the need for a drying room, Our goal is to produce a cell that charges with all Li in the cathode. Therefore, there is no Li metal in the anode-skeleton for the calculation of energy density. [Table 1] The corresponding total energy is E tot =C×V=5.13mAh×6V=30.78mW h. The total volume is 1 cm 2 1.7 x 10 for area -5 L. Therefore, structural The theoretical available specific energy including the bipolar plate is ~603.29Wh / kg. As calculated in the above, the overvoltage at C / 3 is negligible compared to the cell voltage, and this is close to the theoretical value. This results in high energy density at high rates. The bipolar plates provide strength and temperature control is required. This is the required full battery pack specification excluding the external can, since no external can is required (as opposed to In terms of technology, LiBs have an energy density of ~4% from the cell level to the pack level. The corresponding usable energy density of the complete battery pack is ~181 0Wh / L.

[0089] The desirable rate characteristics of SSLiB are due to its three-dimensional (3D) networked skeletal structure. , comparable to those based on organic electrolytes and far superior to traditional planar solid-state batteries. Reasons for this include: The porous SSE scaffolds provide an enlarged 3D electrode-electrolyte interface, a dramatic increase in surface contact area, and and a reduction in charge transfer impedance. Continuous Li + 10 in the electrode scaffold to provide a conductive path -3 ~10 -2 S / Use of SSE with a conductivity of 1.0 MPa. High aspect ratio (lateral dimension vs. thickness) of electrode holes to provide continuous electronic conduction paths Use of graphene (thickness).

[0090] To calculate the rate characteristics, the overpotential of SSLiB shown in Figure 3 was calculated using the electrolyte in Peedance (Z SSE ) and electrode-electrolyte-interface impedance (Z interface )of was estimated including.

[0091] The porous SSE scaffold achieves a smaller interfacial impedance by: Z interface =S*Gs, where S is the interfacial area close to the porous SSE and Gs is The interface impedance is the interface conductance per specific area. The total SS is expected to be small because the active SSE leads to a large electrode-electrolyte interfacial area. The ion transport impedance through the E structure is: ZSSE = Zcathode-skeleton + Zdensity-S SE+Z anode skeleton; and Z=(ρL) / (A*(1-ε)), where ρ=100 Ωcm, L is the thickness (Fig. 3), and A is 1 cm2 ε is the porosity (70% for the cathode skeleton and 50% for the anode skeleton) %, and 0% for the dense SSE layer. Therefore, Z cathode-skeleton = 2.3 Ohm / cm 2 , Z high density-SSE=0.01Ohm / cm 2 , and Z anode-skeleton = 1 Ohm / cm 2 ;As a result Z total =3.31 Ohm / cm 2 At C / 3, the current density degree=1.71mA / cm 2 and the voltage drop is 5.02mV / cm 2 and the 6V cell voltage can be neglected compared to

[0092] The desirable cycling performance is believed to be due to the following advantages: -Intercalated and de-intercalated Li resulting from filling of 3D porous structures There are no structural challenges associated with -3D porous SSE structure provides excellent mechanical and electrochemical stability of the electrolyte-electrode interface . The current state-of-the-art LiB-specific S consumes electrolyte and increases cell impedance. There is no EI formation. - High density ceramic SSE for Li dendrite formation (for LiB with Li anode) (That is the problem.) Therefore, the calendar life should easily exceed 10 years, and the cycle life should easily be It should exceed 5000 cycles.

[0093] The SSLiB is an advancement in battery materials and structures. - It can provide the necessary transformational changes in performance and cost that will drive the electrification of vehicles. As a result, it improves the energy efficiency of vehicles, reduces energy-related emissions, and This will reduce energy imports.

[0094] Figure 4 shows the Li 6.75 BaLa2Ta 1.75 Zinc 0.25 O 12 Including Lithium arsenide The low activation energy of this composition suggests that a similar substitution would result in Li7La3 ZrO 12 If done with, ~10 -2 Scm -1 Pathway to Achieve RT Conductivity It is considered to give

[0095] Garnet SSE can be synthesized as a ceramic powder (unlike LiPON) and therefore has high Fast, scalable multilayer ceramic fabrication technique for tailored nano / micro-structured electrodes It can be used to fabricate thin film (~10 μm) SSEs supported on scaffolds (Figure 3). Tailored porosity (nano / micro features) SSE support layers of 50 and 70 μm followed by colloidal deposition of a ~10 μm dense SSE layer and The resulting pinhole-free SSE layer is due to the support layer. Mechanically robust with a resistance of just ~0.01Ωcm -2 It has a low area specific resistance (ASR).

[0096] The ~6.0 volt cathode composition (Li2MMn3O8, M=Fe, Co) was synthesized. These increase the ionic and electronic conductance, respectively, and reduce the interface impedance. It can be used in conjunction with SSE frameworks and graphene to reduce the Li2 MMn3O8 can be screen printed into a porous cathode framework, and Li-Au The metal can be impregnated into a porous anode skeleton.

[0097] Figure 5 shows the Li-infiltrated porous skeletal anode supported by a thin dense SS E-layer, and solids tested using screen-printed LiFePO4 cathodes The EIS results of the Li cell are shown. The high frequency intercept is The high frequency intercept corresponds to the total cell impedance, and the low frequency intercept corresponds to the total cell impedance.

[0098] The bipolar plate was fabricated by electroplating ~200 Å of Cu on ~40 μm of Al. Due to the three times lower density of Al compared to Cu, the resulting plates are It weighs the same as the combined weight of the ~10μm Al and Cu foils used in the battery. However, it is three times stronger (due to the ~9 times higher strength-to-weight ratio of Al versus Cu). The increase in strength has negligible effect on weight and volumetric energy density or cost. This can be achieved by simply increasing the thickness of the Al plate. SSLiB (bipolar plate) is stacked in series to obtain the desired battery pack voltage. (e.g. 50 6V-S for a 300V battery pack) SLiBs are less than 1cm thick).

[0099] In terms of performance and cost: The energy density of SSLiB shown in Figure 3 is ~600Wh / kg for a 6V cell. The voltage of the Li2FeMn3O8 cathode is 5.5V vs Li. When used, an energy density of 550Wh / kg can be achieved. The energy density calculations in Table 3 take into account the packing for protection against thermal runaway and mechanical losses. Does not include packaging (as this is not required for SSLiB). Includes 20% packaging. Even if this is done, the total energy density is still 500Wh / kg. The ~5mV voltage drop at C / 3 is 10 -2 S / cm ionic conductivity of SSE Based on the idea of ​​a porous SSE framework with a dense SSE layer and corresponding small interfacial charge transfer resistance, (Use 5×10 -4 For an ionic conductivity of 1.0 S / cm, the voltage drop at a rate of C / 3 is only ~0.1V, which is significantly less than the cell voltage of 6V. The cost of materials for SSLiB is much lower than the high SSLiB energy density and the resulting equivalent energy Only $50 / KWh due to the reduction in materials required to achieve this. In terms of cost, our SSLiB is cheaper than the current state of the art because it does not require a drying room. It is thought to be lower than LiB.

[0100] The SSE materials can be synthesized using solid and wet chemical methods. For example, To obtain phase pure substances, the corresponding metal oxides or salts are added to the solid or liquid phases. The powders were mixed as precursors, dried, and synthesized, and heated at 700-1200°C in air. The phase purity can be determined by powder X-ray diffraction (PXRD, D8, Bruker, Cuk α) as a function of synthesis method and calcination temperature. The structure refinement data can be used to determine the metal-oxygen bond lengths and The Li-O bond distance determines the role of dopants in the garnet structure on conductivity. In-situ PXRD shows that as a function of temperature, Some chemistry between garnet-SSE and Li2(Fe,Co)Mn3O8 high voltage cathode The Li-ion conductivity can be used to identify the reactivity of the -dance spectroscopy (EIS-Solartron 1260) and DC (Solartron Potentiostat 1287) four-point method The electrical conductivity can be determined by Li + Blocking Au electrodes and reversible elemental Li The blocking electrode can be used to measure the electrical conductivity of the (transport number measurements), while Li reversible electrode measurements provide the SS Provides information about E / electrode interface impedance. + and other metal ions To understand the role of Li content on ionic conductivity, inductively coupled plasma (ICP) and electron energy loss spectroscopy (EELS). The actual amount of Li and its distribution at different crystallographic sites is important to improve the conductivity. The concentration of mobile Li ions is likely to be important for -2 RT conduction in S / cm is optimized to reach a rate value.

[0101] Sintering of low-density Li-garnet samples is responsible for many of the literature variations in conductivity. (For example, as shown in Fig. 6). The first problem in obtaining a dense SSE is Starting with micron (or nanoscale) powders. Starting with nanoscale powders It is believed that this can reduce the sintering temperature required to obtain a sufficiently dense electrolyte. Nanoscale electrolyte and electrode powders are prepared by co-precipitation, reverse-strike co-precipitation, and Using the precipitation method, the glycine-nitrate method, and other wet synthesis methods These methods can be used to produce the desired Li-garnet composition. and can be used to obtain submicron SSE powders. The SSE powder is then mixed with an appropriate binder and solvent to achieve the desired viscosity and solids content. Can be used to form inks / pastes by mixing with a solvent Dense thin film (~10 μm) garnet SSE on a porous SSE scaffold (e.g., Figure 9b) They can be formed by tape casting (Figure 7a), colloidal deposition, and sintering. The described method uses nano-sized electrodes / electrodes to minimize interfacial polarization (e.g., Fig. 7c). The symmetric framework / SSE shown in FIG. / The skeleton structure is laminated to the skeleton / SSE layer using a heated lamination press in the green state It can be constructed by laminating another skeleton layer (before sintering).

[0102] Cathode and anode assembly Nano-sized (~100 nm) cathode materials, Li2MMn3O8 (M=Fe, Co) By using SSE, which is stable up to 6 V, a specific capacity of 300 mAh / g can be achieved. The cathode material slurry is composed of 10% (by weight) carbon black and 5% % (by weight) of N-methyl-2-pyridinium fluoride (PVDF) polymeric binder The nanoparticles can be prepared by dispersing them in a nitric oxide (NMP) solution. The slurry was then deposited on the porous SSE scaffold by drop casting. To dry the solvent and increase the electrode-electrolyte interfacial contact, The SSE with the cathode material is then heated at 100° C. for 2 hours. Further heat treatment improves the interface It may be necessary to optimize the viscosity of the slurry to achieve the desired packing. The viscosity of the binder / solvent mixture is controlled by modifying the solids content and binder / solvent concentration to achieve the desired viscosity. The cathode particle size may be varied to control pore filling into the SSE. In the example, all the mobile Li comes from the cathode (the anode SSE framework is the electron transporter in the cell). It may be coated with a thin layer of graphite material by solution processing to initiate conduction. In another example, a thin layer of Li metal is infiltrated inside the anode SSE skeleton and conforms to the shape of the Mild heating (~400°C) of Li metal foil or commercially available nanoparticles can be used to The excellent wettability between Li metal and the SSE is This was achieved by modifying the surface of the SSE scaffold (Figure 8). To fill the pores of E with highly conductive graphitic material, a graphene dispersion was prepared by known methods. For example, by matching the surface energy between graphene and the mixed solvent, Graphene flakes at 1 mg / mL can be dispersed in water / IPA solvent. The drop coating is a ~10 nm thick conductive glass coating on the inside of a porous SSE anode scaffold. After successfully filling the pores of the framework, the metal current collector can be used to deposit rhenium. The cell can be completed using Al foil for the cathode and Cu foil for the anode. Bipolar metal can be used for stacking and integration of cells. To improve the electrical contact between the electrode and the current collector, a thin A graphene layer may be applied. The completed device may further include electrical contacts between the layers. It may be heated to 100°C for 10 minutes to improve the electrochemical performance of SSLiB. The results were analyzed by cyclic voltammetry, constant current charging and discharging at various rates, and electrochemical induction. by impedance spectroscopy (EIS), and cycling performance at C / 3 EIS can be used to investigate the various contributions to device impedance and By comparing the EIS of a control cell with a Li-metal electrode and a cathode, the SSE In order to clarify the interface impedance between the z) can be used in the SSE, the electrode, the SSE-electrolyte interface, and the current collector-electrode. The energy density, power density, rate dependence, and cycle dependence of each cell as a function of interface were The performance of the system can be determined.

[0103] Multi-cell (2-3 cells in series) SSLiB with Al / Cu bipolar plates is now available for production. The energy / power density and mechanical strength can be determined as a function of layer thickness and area.

Claims

1. 1. A solid-state ionically conductive battery, comprising: a) a cathode or anode material; b) a solid electrolyte (SSE) material including a porous region having a plurality of pores and a dense region; Here, the cathode material or the anode material is disposed in at least a portion of the porous region. the high density region being free of the cathodic and anodic materials; and c) a collection material disposed in contact with at least a portion of the cathodic or anodic material; Electrical equipment Including battery.

2. The SSE material includes the two porous regions, the cathode material, and the anode material. The cathode material is present in at least one of the porous regions forming the cathode-side porous region. The anode material is disposed in the other porous region forming the anode-side porous region. The cathode side region and the anode side region are disposed in at least a part of the high The cathode side current collector and the anode side current collector are disposed on opposite sides of the density region. The solid-state, ionically conductive battery of claim 1.

3. The cathode material is a lithium-containing material, a sodium-containing cathode material, or a magnesium-containing cathode material.

3. The solid-state ionically conductive battery of claim 1 or 2, wherein the cathode material is a cation-containing cathode material. 。

4. The cathode material comprises a conductive carbon material, and the cathode material optionally further comprises: The solid lithium battery according to claim 1 or 2, further comprising an organic or gel ion-conducting electrolyte. Um-ion battery.

5. The lithium-containing electrode material is LiCoO 2 , LiFePO 4 , Li 2 M.M. 3 O 8 mosquito The lithium-containing ion-conducting cathode material is selected from the group consisting of Fe, Co, and and combinations thereof. 。

6. The sodium-containing cathode material is Na 2 V 2 O 5 , P2-Na 2/3 Fe 1/2 M n 1/2 O 2 、Na 3 V 2 (PO 4 ) 3 、NaMn 1/3 Co 1/3 Ni 1/3 PO 4 、お Yobi Na 2/3 Fe 1/2 Mn 1/2 O 2 and a composite of graphene, The cathode material according to any one of claims 3 to 5, which is a sodium-containing ion-conducting cathode material. of solid-state ionic conductive batteries.

7. The magnesium-containing cathode material is a magnesium-containing ion-conducting cathode material. and is a doped manganese oxide. -

8. The anode material may be a lithium-containing anode material, a sodium-containing anode material, or The solid ion cathode material according to any one of claims 3 to 7, wherein the anode material is a magnesium-containing anode material. Conductive battery.

9. The solid state ion conductor of claim 8, wherein the lithium-containing anode material is lithium metal. Conductive battery.

10. The sodium-containing anode material is sodium metal or Na 2 C 8 H 4 O 4 oh Yobi Na 0.66 Li 0.22 Ti 0.78 O 2 Ionic conductivity selected from sodium 10. The solid-state, ionically conductive battery of claim 8, wherein the anode material is a ruthenium-containing anode material.

11. 9. The solid-state anode material of claim 8, wherein the magnesium-containing anode material is magnesium metal. Ion conductive battery.

12. The SSE material is a lithium-containing SSE material, a sodium-containing SSE material, or a magnesium-containing SSE material. The solid ion conducting nanotube according to any one of claims 3 to 11, which is a nesium-containing SSE material. Sexual battery.

13. The lithium-containing SSE material according to claim 12, wherein the lithium-containing SSE material is a Li-garnet SSE material. Solid-state ionic conductive battery.

14. The Li-garnet SSE material is a cation-doped Li 5 La 3 M 1 2 O 12 (M 1 is Nb, Zr, Ta, or a combination thereof), cation-doped Li 6 La 2 Ba T 2 O 12 , cation-doped Li 7 La 3 Zr 2 O 12 , and cation-doped Li 6 BaY 2 M 1 2 O 12 where the cation dopants are barium, yttrium , zinc, or a combination thereof. Battery.

15. The Li-garnet SSE material is Li 5 La 3 Nb 2 O 12 , Li 5 La 3 T 2 O 12 、 7 Lạ 3 Zr 2 O 12 、 6 Lạ 2 SrNb 2 O 12 、 6 Lạ 2 Ba Nb 2 O 12 、 6 Lạ 2 rTa 2 O 12 、 6 Lạ 2 BaTa 2 O 12 、 7 Y 3 Zr 2 O 12 ,Li 6.4 Y 3 Zr 1.4 Ta 0.6 O 12 ,Li 6.5 La 2.5 Ba 0.5 TaZrO 12 、Li 6 BaY 2 M 1 2 O 12 、Li 7 Y 3 Zr 2 O 12 、L i 6.75 BaLa 2 Nb 1.75 Zn 0.25 O 12 、 or Li 6.75 BaLa 2 T 1.75 Zinc 0.25 O 12 The solid-state lithium ion battery according to claim 13, Lee.

16. The current collector according to any one of claims 12 to 15, wherein the current collector is a conductive metal or metal alloy. The solid-state ionically conductive battery described herein.

17. The high density region of the SSE material has a dimension between 1 μm and 100 μm, and / or The porous region of the SSE material in which the cathode material is disposed is between 20 μm and 200 μm. A porous region of the SSE material having a dimension and / or in which the anode material is disposed.

17. The solid, ionically conductive bag of claim 16, wherein the regions have dimensions between 20 μm and 200 μm. Terry.

18. the ion-conducting cathode material, the ion-conducting anode material, the SSE material, and and the current collector form a cell, and the solid-state ion conductive battery includes a plurality of pre- 2. The method of claim 1, further comprising:

18. The solid-state ionically conductive battery according to claim 6 or 17.

19. A solid electrolyte (S) comprising a porous region of electrolyte material disposed on a dense region of electrolyte material. A solid-state ionically conductive battery having a SSE material, the SSE material being an ion diffuses into the porous region of the SSE material during charging and / or discharging of the battery; and a battery configured to diffuse therefrom.

20. The SSE material has two porous regions disposed on either side of a dense region of the SSE material.

20. The solid-state, ionically conductive battery of claim 19, having

Citation Information

Patent Citations

  • Manufacturing method of solid electrolyte structure for all-solid battery, and manufacturing method of all-solid battery

    JP2008226666A

  • Garnet-type lithium ion-conducting oxide

    JP2010202499A

  • Method for filling with electrode active material and method for manufacturing all-solid-state cell

    JP2010218686A

  • Chemically stable solid lithium ion conductor

    US20070148553A1

  • Solid electrolyte structure for all-solid-state battery, all-solid-state battery, and their production methods

    WO2008059987A1